Sistem Pengontrolan Lampu Cerdas Berbasis Aplikasi Android - Andi Maulidinnawati Abdul Kadir Parewe, Akbar iskandar, Suriani (Celebes Computer Science Journal, 2019)
The purpose of the device developed in this study is to control the lights by implementing the Android system. This data is obtained through field observations and literature reviews related to android-based light control and literature review on design and application of the android system. The results of the design and analysis of this study show that the system being developed can work as expected in accordance with the research objectives. The control light application program that has been made has met and is running on the system or android application, besides that it can make the lights turn on and off the lamp hardware, which uses 8 lights. The communication known as data communication between the light path and the Android smartphone can run as desired because it runs well and the range of the system developed for control applications that can control the light device according to the specifications of the wireless device used both from the receiving and sending sides.